Is glucose-6-phosphate dehydrogenase deficiency associated with COVID-19 infection, severity, and death? A cohort study from the Brazilian Amazon - Adila L. B. Dias; Joabi Rocha Nascimento; José Diego Brito-Sousa; Marco Aurelio Sartim; Kamilla Freitas da Silva; Alexandre Vilhena Silva-Neto; Gabriel dos Santos Mouta; Patricia Carvalho da Silva Balieiro; Djane Clarys Baía-da-Silva; Fernando Almeida-Val; Gisely Cardoso de Melo; Vanderson de Souza Sampaio; et al. (PLoS ONE, 2025)
Background Glucose-6-phosphate dehydrogenase deficiency (G6PDd) is a common genetic disorder that impairs the cellular antioxidant response and has been hypothesized as a potential risk factor for severe outcomes in viral infections, including COVID-19. However, clinical evidence remains limited, especially in regions with high G6PDd prevalence. Methods We conducted a retrospective cohort study using secondary data from four health information systems from health facilities in the Brazilian Amazon (E-SUS Notifica, SIVEP-Gripe, SIM, and a G6PD enzyme activity database). The study population consisted of 3,955 male participants, including 206 with confirmed G6PDd. We used logistic regression to assess associations between G6PDd and COVID-19 infection, hospitalization, and death. Cox proportional hazards models and Kaplan-Meier curves were applied to evaluate time-to-event outcomes. Results No statistically significant association was found between G6PDd and SARS-CoV-2 infection (OR = 1.15; 95% CI: 0.70–1.79; p = 0.6), hospitalization (OR = 1.13; 95% CI: 0.27–3.20; p = 0.8), or death (OR = 0.00; p > 0.9). Age was a significant risk factor for all outcomes, and individuals identified as Asian had a higher likelihood of infection (OR = 2.87; 95% CI: 1.57–5.29; p < 0.001). Conclusion In this cohort from the Brazilian Amazon, G6PD deficiency was not associated with an increased risk of COVID-19 infection or severe outcomes. These findings emphasize the importance of considering ethnic and genetic diversity in epidemiological analyses and health policy planning, particularly in regions with high G6PDd prevalence.